Overcoming wound complications in head and neck salvage surgery. Issue 6 (December 2018) - Kwon, Daniel; Genden, Eric M.; de Bree, Remco; Rodrigo, Juan P.; Rinaldo, Alessandra; Sanabria, Alvaro; Rapidis, Alexander D.; Takes, Robert P.; Ferlito, Alfio
Abstract: Background: Loco-regional treatment failure after radiotherapy with or without chemotherapy and/or prior surgery represents a significant portion of head and neck cancer patients. Due to a wide array of biological interactions, these patients have a significantly increased risk of complications related to wound healing. Methods: Review of the current literature was performed for wound healing pathophysiology, head and neck salvage surgery, and wound therapy. Results: The biology of altered wound healing in the face of previous surgery and chemoradiotherapy is well described in the literature. This is reflected in multiple clinical studies demonstrating increased rates of wound healing complications in salvage surgery, most commonly in the context of previous irradiation. Despite these disadvantages, multiple studies have described strategies to optimize healing outcomes. The literature supports preoperative optimization of known wound healing factors, adjunctive wound care modalities, and microvascular free tissue transfer for salvage surgery defects and wounds. Conclusion: Previously treated head and neck patients requiring salvage surgery have had a variety of disadvantages related to wound healing. Recognition and treatment of these factors can help to reverse adverse tissue conditions. A well-informed approach to salvage surgery with utilization of free vascularized or pedicled tissue transfer as well as optimizing wound healing factors is essential to obtaining favorable outcomes.